Family planning and the handicapped - C. Welman (AOSIS, 1982)
People tend to ignore the fact that sexual relationships are as important for the disabled as for the normal individual. Health professionals often do not recognise that disabled individuals are capable of enjoying and taking part in a full range of sexual activities. There are many problem areas which need to be considered but, with regard to family planning, counselling is of paramount importance.